Islamic Education as an Agent of Social Transformation: A Pedagogical and Socio-Cultural Perspective - Amir Mahmud; Febri Bekti Pangestu; Aboubacar Barry (Pascasarjana Universitas KH. Abdul Chalim, 2026)
This article examines Islamic Religious Education (IRE) as an agent of social transformation in the context of socio-cultural change, digital disruption, and literacy challenges. The study aims to analyze how Islamic education operates as a pedagogical, cultural, and institutional practice that shapes public ethics, critical awareness, and students' social participation. This research employed a qualitative, educational ethnographic design at SMA Muhammadiyah 4, Andong, Boyolali, Central Java. Data were collected through participatory observation, in-depth interviews with IRE teachers, school leaders, student activity advisors, and students, as well as documentation of curriculum materials, school programs, and cultural artifacts. Data were analyzed thematically through coding, theme development, and interpretive meaning-making. The findings show that Islamic school culture functions as a collective moral language, IRE pedagogy moves between normative transmission and critical dialogue, and digital transformation produces micro-justice practices based on Islamic values. The article contributes to strengthening the perspective of Critical Islamic Pedagogy by integrating pedagogical, leadership, and socio-cultural dimensions in explaining the role of IRE as an agent of social transformation.